Incremental Policy in the Development of Madrasahs and Islamic Boarding Schools: A Review of Lindblom's Incrementalism Theory in the Contemporary Era - Ati Rahmawati; Mukhlis (Formad English Foundation NTB-Jakarta, 2026)
The development of madrasahs and Islamic boarding schools in Indonesia has increasingly required policy approaches capable of balancing educational modernization with the preservation of Islamic traditions. However, limited studies have examined this development from the perspective of Charles E. Lindblom's incrementalism theory. This study aimed to analyze how incremental policy characterizes the contemporary development of madrasahs and Islamic boarding schools and to identify the factors influencing the incremental policy process within these Islamic educational institutions. The research employed a qualitative library research design using official government policy documents, scholarly books, peer-reviewed journal articles, and other relevant academic publications as primary data sources. Data were analyzed through qualitative content analysis involving data reduction, thematic categorization, interpretation, and source triangulation. The findings reveal that the development of madrasahs and Islamic boarding schools consistently follows an incremental policy trajectory characterized by gradual improvements in educational regulations, curriculum and learning systems, teacher professional development, institutional governance, and educational financing. The study also demonstrates that institutional leadership, organizational capacity, government support, educational decentralization, socio-cultural values, political commitment, bureaucratic coordination, digital transformation, and globalization collectively influence the continuity of incremental policy development. These findings confirm the continued relevance of Lindblom's incrementalism theory in explaining policy change within Islamic education and suggest that gradual policy adaptation provides an effective mechanism for maintaining institutional stability while encouraging sustainable educational innovation. The study contributes to both public policy and Islamic education literature by offering a comprehensive conceptual understanding of incremental policy development in contemporary Islamic educational institutions.